2015
DOI: 10.1589/jpts.28.142
|View full text |Cite
|
Sign up to set email alerts
|

Association between the physical activity level and the quality of life of patients with type 2 diabetes mellitus

Abstract: [Purpose] Physical activity and regular exercise play an important role in glycemic control, which is considered an important part of the treatment of type 2 diabetes mellitus. This study evaluated physical activity level and its relationship with quality of life in patients with type 2 diabetes mellitus. [Subjects and Methods] We evaluated 129 subjects with type 2 diabetes mellitus through a face-to-face interview using the short version of the International Physical Activity Questionnaire and Diabetes-39. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 31 publications
6
35
1
Order By: Relevance
“…All three studies which included a comparison group report people with T2D to have higher levels of SB than those without T2D . Studies which subjectively measured SB report variable outcomes including: >3 hours/day watching TV (38.1%); mean sitting time/day (4.8–5.8 hours); and mean sitting time/week (302 minutes/week) …”
Section: Resultsmentioning
confidence: 99%
“…All three studies which included a comparison group report people with T2D to have higher levels of SB than those without T2D . Studies which subjectively measured SB report variable outcomes including: >3 hours/day watching TV (38.1%); mean sitting time/day (4.8–5.8 hours); and mean sitting time/week (302 minutes/week) …”
Section: Resultsmentioning
confidence: 99%
“…[67][68][69][70] It is shown they can improve blood glucose control, reduce cardiovascular risk factors, improve well-being and assist in weight loss. [71][72][73] An exercise intervention of a period of eight weeks at least, can reduce the level of HbA1c by 0.66% in people with DM, even if there is no weight loss. People with DM should be advised to break the time they spend being sedentary with brief standing, walking or performing other light activities.…”
Section: Physical Activitymentioning
confidence: 99%
“…However, the QOL of people with type 2 diabetes remains low, and this is a major social issue. [7][8][9] Factors influencing QOL include physical, social, and psychological conditions. One previous study showed that improvements in exercise habits and diet resulted in better QOL, 8 suggesting that self-management of diet and exercise are necessary for improving QOL.…”
mentioning
confidence: 99%